2019
DOI: 10.1136/bmjopen-2018-023849
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of fetal loss in Chinese pregnant patients with systemic lupus erythematosus: a retrospective cohort study

Abstract: ObjectiveTo develop a predictive model for fetal loss in women with systemic lupus erythematosus (SLE).DesignA retrospective cohort study.SettingData were collected in a tertiary medical centre, located in Shanghai, China, from September 2011 to May 2017.Participants338 pregnancies with SLE were analysed retrospectively. Cases of multiple pregnancy and those in which artificial abortion was performed for personal reasons were excluded.Primary outcome measuresFetal loss was the primary outcome. A stepwise regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…These have included the presence of renal involvement or active nephritis, [ 20 , 24 , 47 53 ] SLE flares during pregnancy, [ 7 , 24 , 50 , 53 , 54 ] active disease prior to or during pregnancy, [ 20 , 50 , 54 56 ] hypertension, [ 7 , 24 , 25 , 54 57 ] presence of anti-phospholipid antibodies (APL) and/or lupus anti-coagulants, [ 7 , 20 , 23 , 24 , 50 , 53 , 54 , 56 , 57 ] cytopenia, [ 41 , 50 , 52 , 54 ] and hypocomplementemia. [ 20 , 25 , 50 , 54 , 56 , 58 , 59 ] This study also confirmed that renal involvement during pregnancy was associated with poor pregnancy outcomes, in both the fetus and mother. However, the presence of hypertension only associated with maternal flares.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These have included the presence of renal involvement or active nephritis, [ 20 , 24 , 47 53 ] SLE flares during pregnancy, [ 7 , 24 , 50 , 53 , 54 ] active disease prior to or during pregnancy, [ 20 , 50 , 54 56 ] hypertension, [ 7 , 24 , 25 , 54 57 ] presence of anti-phospholipid antibodies (APL) and/or lupus anti-coagulants, [ 7 , 20 , 23 , 24 , 50 , 53 , 54 , 56 , 57 ] cytopenia, [ 41 , 50 , 52 , 54 ] and hypocomplementemia. [ 20 , 25 , 50 , 54 , 56 , 58 , 59 ] This study also confirmed that renal involvement during pregnancy was associated with poor pregnancy outcomes, in both the fetus and mother. However, the presence of hypertension only associated with maternal flares.…”
Section: Discussionsupporting
confidence: 74%
“…Active SLE was an independent predicting factor for SLE flares and lupus nephritis, while SLE flares and the presence of APL antibodies were independent predicting factors for pre-eclampsia among mothers. Wu et al [ 59 ] recently found that unplanned pregnancy, hypocomplementemia and urine protein >1.0 gm/day were independent predicting factors for fetal loss. This study found that age >25 years and ever having renal involvement were independent predicting factors for fetal loss, renal involvement during pregnancy, prematurity, SGA and LBW among infants.…”
Section: Discussionmentioning
confidence: 99%
“…However, other measures such as a predictive model for fetal loss to identify high risk pregnancies, as shown in a Chinese retrospective study might be helpful to these women with SLE. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Foetal APOs included one or more of the following: (1) foetal loss—spontaneous abortion (referring to termination before 28 weeks of pregnancy with foetal weight less than 1000 g), therapeutic abortion (iatrogenic abortion caused by a lupus flare or obstetric complications threatening the life of the mother), stillbirth (any baby born without signs of life at ≥28 completed weeks of gestation), and neonatal death (death of a liveborn baby within 28 days after birth) 15 ; (2) premature birth—delivery prior to 37 weeks of gestation 16 ; (3) SGA—birth weight below the 10th percentile according to gestational week at delivery and foetal sex 17 ; and (4) asphyxia neonatorum—Apgar score of <7 at 1 and/or 5 min after birth. 18 Composite foetal APOs were defined as the occurrence of any adverse outcomes, including foetal loss, premature birth, SGA and asphyxia neonatorum.…”
Section: Methodsmentioning
confidence: 99%